Effect of Type of Cow-Calf Contact on Health, Blood Parameters, and Performance of Dairy Cows and Calves - Wenker, Margret L.; Verwer, Cynthia M.; Bokkers, Eddie A. M.; te Beest, Dennis E.; Gort, Gerrit; de Oliveira, Daiana; Koets, Ad; Bruckmaier, Rupert M.; Gross, Josef J.; van Reenen, Cornelis G. (Frontiers in Veterinary Science, 2022)
Prolonged cow-calf contact (CCC) could potentially improve dairy calf welfare. However, it is currently unknown how different types of CCC affect the animals’ biological functions. We evaluated health and performance parameters of dairy calves and their dams that were allowed to have either: i) no contact (NC); the calf was removed from the dam directly after birth (n=10), ii) partial contact (PC); the calf was housed in a calf pen adjacent to the cow area allowing physical contact on initiative of the dam but no suckling (n=18), or iii) full contact (FC), including suckling; calves were housed together with their dams in a free stall barn (n=20). Throughout the first 7 weeks postpartum, data were collected on the health status, fecal microbiota, hematological profile, immune and hormonal parameters, and growth rates of calves, and on the health status, metabolic responses, and performance of dams. Overall, FC calves had more health issues (P=0.02) and a tendency for higher antibiotic usage (P=0.07) than NC calves. Additionally, FC calves showed elevated levels of erythrocytes, hematocrit, hemoglobin, and leukocytes on day 49 compared to NC calves (P<0.001). Calf fecal microbiota changed over time and we found preliminary evidence that fecal microbiota are affected by type of CCC, as reflected by differences in relative abundances of taxa including Lactobacillus in FC calves compared to NC and PC calves except on day 7 and 66. The FC calves had a greater average daily gain in body weight than NC and PC calves (P=0.002). Cow health was not affected by type of CCC, although in the first 7 weeks of lactation FC cows had a lower machine-gained milk yield accompanied by a lower fat percentage than NC and PC cows (P<0.001). These results indicate that full contact posed a challenge for calf health, presumably because the housing conditions of FC calves in this experimental context were suboptimal. Secondly, ad libitum suckling lead to higher weight gains and negatively affected milk fat content besides machine-gained yields. More research into strategies to improve cow-calf housing and management in CCC systems is warranted.